2012
DOI: 10.1111/bjso.12005
|View full text |Cite
|
Sign up to set email alerts
|

Nations' income inequality predicts ambivalence in stereotype content: How societies mind the gap

Abstract: Income inequality undermines societies: the more inequality, the more health problems, social tensions, and the lower social mobility, trust, life expectancy. Given people’s tendency to legitimate existing social arrangements, the Stereotype Content Model (SCM) argues that ambivalence—perceiving many groups as either warm or competent, but not both—may help maintain socio-economic disparities. The association between stereotype ambivalence and income inequality in 37 cross-national samples from Europe, the Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
255
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 193 publications
(286 citation statements)
references
References 84 publications
16
255
0
3
Order By: Relevance
“…The results supported the application of the SCM on the Swedish stereotype of the poor, and fit well with earlier findings regarding this stereotype in other countries (cf. Asbrock, 2010;Bye et al, 2014;Cuddy et al, 2008;Durante et al, 2013): The content of the stereotype of poor people consists of relatively low ratings on both competence and warmth (i.e. LC-LW or LC-L/MW), always with a higher rating on warmth than competence.…”
Section: Discussionmentioning
confidence: 99%
“…The results supported the application of the SCM on the Swedish stereotype of the poor, and fit well with earlier findings regarding this stereotype in other countries (cf. Asbrock, 2010;Bye et al, 2014;Cuddy et al, 2008;Durante et al, 2013): The content of the stereotype of poor people consists of relatively low ratings on both competence and warmth (i.e. LC-LW or LC-L/MW), always with a higher rating on warmth than competence.…”
Section: Discussionmentioning
confidence: 99%
“…Durante et al [18,19] provides some initial evidence for this hypothesis. In a study including 37 samples from 27 nations, it was found that higher inequality lowered warmth perceptions of those higher in socio-economic status and led to increased incompetence perceptions of people lower in SES [19].…”
Section: Why Income Inequality Is Harmful For Intergroup Relations Inmentioning
confidence: 96%
“…This space usefully describes a variety of human social perceptions: over US samples, both convenience [students, adults (23)] and representative [adults (24)]; over dozens of countries, using their own social groups (26,27); over time [Italian Fascists (28); American students since 1933 (29)]; over levels of analysis, from individuals (30) to subtypes of women and men (31), immigrants (32), gay men (25), and African Americans (33); and even over other intent-having entities, such as animal species* and corporations (34,35). These warmth-by-competence data suggest the bold conclusion that the dimensions are universally descriptive of group images.…”
Section: Identifying Whom To Trustmentioning
confidence: 99%